Analisis Tingkat Kepuasan Anggota Kelompok Petani Padi Di Kecamatan Sungai Kakap (Jurnal Agribisnis Indonesia, 2025)
This study comprehensively examines the satisfaction levels of rice farmer group members in Desa Sungai Itik, Kecamatan Sungai Kakap, Kabupaten Kubu Raya. It focuses on evaluating the farmers’ satisfaction with the quality of services provided by the farmer groups. Utilizing comprehensive analysis methods, namely Importance-Performance Analysis (IPA) and Customer Satisfaction Index (CSI), the data analysis revealed that farmers in Sungai Itik Village generally feel satisfied with various service aspects delivered by the farmer groups. This is reflected in the Customer Satisfaction Index (CSI) score, which reached 79.16%. However, the study also identified several gaps between farmers’ expectations and the reality of services received. One key issue highlighted is the responsiveness and accuracy of the management in addressing member complaints. Additionally, the implementation of Annual General Meetings (RAT) was noted as an area of concern, with farmers expecting more regular and participatory meetings. Through IPA analysis, several service aspects were found to have a strong influence on farmers' satisfaction levels. The skills and knowledge of farmer group management, as well as their friendliness in interacting with members, were identified as key factors shaping farmers’ perceptions of service quality. This indicates that enhancing the management’s capacity through training and development is a strategic step to improve member satisfaction. The study recommends providing training for the management and conducting regular evaluations to enhance the performance of farmer groups in the future, aiming to achieve a higher level of satisfaction.